The Inhibitory Effect of Manganese Oxide Nanoparticles Synthesized by Prodigiosinagainst Pathogenic P. aeruginosa - Minshed, Noor J.; Younis, Reem W. (Iraqi Journal of Science, 2024)
The present work aims to biosynthesis of manganese oxide nanoparticles (MnO NPs) using Prodigiosin pigment, produced by Serratia marcescens, as a stabilizing and reducing agent. In addition to the characterizing of the biosynthesized MnO NPs were characterized utilizing several optical methods, including FT-IR, XRD, AFM and UV-Vis. A cut-off wavelength of the biologically synthesized MnO NPs was established at around 440 nm using UV-Vis. Furthermore, the analysis of AFM revealed that MnO NPs have an average diameter size of 74.51 nm. The results showed concentration-dependent antibacterial effect (25, 50, 100 and 200 mg/ml) of MnO nanoparticles on Pseudomonas aeruginosa. Overall, it is concluded that the biosynthesized MnO NPs retain the potential to serve as an alternative antibacterial agents.